ANALISIS PEMOTONGAN PIPA PRODUKSI SUMUR MINYAK DENGAN TEKNIK HYDRAJETTING MENGGUNAKAN FLUIDA ABRASIF DAN POMPA BERTEKANAN TINGGI - Komarudin, Komarudin; Kalangsunda, Taufik Rachmat Rakean (Bina Teknika, 2019)
An oil production well own by Company X had its production declined due to the impact of corrosion and scaling issues which happened on the production tubing. To solve the problem, an immediate action was made to replace the production tubing through a Hydrajetting cutting process which combining the abrasive fluid and high pressure pump application.The scope of subject were limited to process analyzing and calculation which happened during the production tubing cutting process. Analysis was done through fluid mechanic principle with the usage of the Energy Conservation Theory to get an accurate result of a successful Hydrajetting cutting process for production tubing. Analysis method was used to calculate all the data which includes fluid velocity, pressure, energy, and all the other related factors. The result of the calculation will be compared to the Hydrajetting recommendation standard.The result from the analysis will prove and explain a successful Hydrajetting cutting process for production tubing and provide a quality measured solution to solve the problem happened on the oil production well due to damage occurred on its production tubing.